Description of Folk Games in the Ghazal’s of Alisher Navoi (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article analyzes the artistic depiction of the folk game of ghazal from the collection “Garaib us-sigar” by Alisher Navoi. Navoiʻs artistic mastery is revealed through the example of the depiction of folk games.